IS THERE ANY DIFFERENCE IN LOCOREGIONAL RECURRENCES AFTER CONSERVING BREAST SURGERY IN PATIENTS OVER 70 YEARS OLD COMPARED WITH PATIENT BELOW? - Antonini, Marcelo; Solino, Matheus de Paula; Cardoso, Mariana Soares; Ferraro, Odair; Lopes, Reginaldo Guedes Coelho; Real, Juliana Monte (Mastology, 2026)
Objective: The aim of the study was to assess whether the type of surgical treatment has an impact on local recurrence and overall survival (OS) of patients aged 70 years or older when compared to patients below 70 years of age. Methods: This is a retrospective case-control study. Data were collected from the medical records of all female patients undergoing surgical treatment for breast cancer at the Hospital do Servidor Público Estadual de São Paulo (HSPE) between March 2014 and October 2020. Female patients with a diagnosis of malignant neoplasm of the breast confirmed by the pathological anatomy exam and submitted to surgical treatment at some stage of the follow-up (1,120 patients) were included in the study. Patients whose medical records did not present complete data (37) and the presence of metastasis at diagnosis (6) were excluded. The final sample contained 1,077 patients. For continuous variables, the mean and standard deviation were calculated; for categorical variables, frequency and percentage were calculated. To compare the variables of interest by age group, the chi-square test was used. When necessary, the Fisher’s exact test or the likelihood ratio test was used. To compare OS, relapse-free survival, and metastasis-free survival by age group, the log rank (Mantel-Cox) test was used, and when necessary, the Breslow test was used. The curves were fitted by Kaplan-Meier. A significance level of 5% was used (p-value<0.05). Results: Local recurrences occurred in 61 patients (5.7%) with a mean time of 24 months after diagnosis, and 120 (11.2%) patients had distant metastasis at a mean time of 23 months. There were 96 deaths (8.9%), of which 73 were from neoplastic causes (78.5%) on average 30 months after diagnosis. The mean follow-up time was 47 months, the overall survival was 45 months, and the disease-free survival was 43 months. Patients were divided into groups aged up to 69 years (G1) and 70 years or older (G2). G1 was composed of 808 (75%) patients and G2 of 269 (25%) patients. The comparative analysis of the groups showed a statistically significant difference in specific clinical stages: G1 had more clinical stage IIIA and G2 had IIA and IIIB. There was no statistically significant difference in estrogen receptor, progesterone receptor, and HER2 positivity; however, G1 had a higher Ki-67 mean (p<0.05). There was a statistically significant difference in the indication of breast-conserving surgery with patients from G1 being more frequently submitted to this type of treatment. There was no significant difference in the variables of recurrent local (RL), metastasis, and their respective times. Among the patients who underwent breast-conserving surgery, there was no statistically significant difference in RL and metastasis; however, the patients in G1 who underwent breast-conserving surgery relapsed in a shorter time than those in G2: 28×39 months − p<0.05. There was no difference between the groups regarding disease-free survival; however, the OS was higher among patients in G1 (p<0.05). Conclusion: This study presented data that showed no statistically significant difference in locoregional recurrence rates between patients under 70 years of age and patients aged 70 years and above. Those, however, had higher OS.